Manajemen Strategis dalam Menghadapi Tantangan Globalisasi : Integrasi Teknologi, Budaya, dan Keberlanjutan untuk Daya Saing Global - Sukardi Sukardi; Nurhayati Nurhayati; Fuad Siregar (Jurnal Visi Manajemen, 2024)
Globalization has created new challenges for companies to enhance their competitiveness in the global market. The rapidly changing business environment requires the adoption of effective strategic management, including technological innovation, cultural adaptation, sustainability, and human resource management. This study aims to analyze these factors in addressing globalization challenges and provide practical recommendations for companies. The research employs a descriptive qualitative method, with data collection through in-depth interviews, observations, and document analysis. The study was conducted over three months with companies from various industrial sectors as subjects. The findings indicate that companies capable of integrating technological innovation and cultural adaptation gain a greater competitive advantage in the global market. Additionally, sustainability and human resource management play critical roles in supporting the implementation of global strategies. However, the greatest challenge is faced by SMEs, which encounter resource limitations in adopting global strategies. The implications of this research highlight the need for government support to accelerate digitalization and enhance human resource capacity. Future researchers are recommended to examine the role of government policies in strengthening the global competitiveness of small and medium enterprises.